Knowledge and Attitude Regarding Blood Donation among First-Time Blood Donor Students of Selected Colleges - Ceena Bejoy; Sucheta Yangad; Sneha Yadav; Khurshid Jamadar; Sadhana Adhyapak; Jyotishree Mishra (Journal of Pharmacy and Bioallied Sciences)
Background: Ensuring a continuous supply of safe blood is critical for effective healthcare. Educating students about blood donation can improve the number of voluntary donors. Understanding the knowledge and attitudes of first-time donors is key to fostering a culture of blood donation. Materials and Methods: This descriptive survey utilized a structured questionnaire to assess the knowledge and attitudes of 265 students from selected colleges. Reliability tests yielded R-values of 0.96 for knowledge and 0.95 for attitudes. Results: Of the 265 students, 58.9% had poor knowledge, 26% had average knowledge, and 15.1% had good knowledge. Attitudes were more favorable, with 55.8% showing the most favorable attitude. The correlation coefficient between knowledge and attitude was 0.16, indicating a weak but positive correlation. Conclusion: Despite low knowledge levels, most students exhibited favorable attitudes toward blood donation. Targeted educational interventions could improve both knowledge and donation rates among students.